Housing safety and health academic and public opinion mining from 1945 to 2021: PRISMA, cluster analysis, and natural language processing approaches - Li, Na; Li, Rita Yi Man; Yao, Qi; Song, Lingxi; Deeprasert, Jirawan (Frontiers in Public Health, 2022)
Housing safety and health problems threaten owners' and occupiers' safety and health. Nevertheless, there is no systematic review on this to the best of our knowledge. This paper compared the academic and public opinions on housing safety and health. It reviewed 982 research papers and 3,173 authors who published housing safety and health in the Web of Science core collection. PRISMA filtered the data, and Natural Language Processing (NLP) analyzed the abstracts' emotions. Only 16 housing safety and health papers worldwide existed before 1998 but rose afterwards. The US scholars published most research papers (30.76%). All top ten most productive countries were developed countries except China, which ranked second (16.01%). Only 25.9% of institutions have inter-institutional cooperation, and collaborators from the same institution produce most work. This study found that most abstracts were positive (n=521), but abstracts with negative emotions attracted more citations. Despite many industries moving toward AI, housing safety and health research are exceptions per articles published and Tweets. On the other hand, this study reviewed 8257 Tweets to compare the focus of the public to academia. There were substantially more housing/residential (n=8198) safety papers than health (n=59), which is the opposite of academic research. Most Tweets about housing/residential safety were UK/Canada, while housing health hazards were from India. The main concern about housing safety per Twitter includes finance, people and threats to housing safety. In contrast, people are mainly concerned about housing health issues' costs, covid and air quality. Besides, most housing safety Tweets were neutral but positive dominated residential safety and health Tweets.